Antagonistic effects of a covalently dimerized insulin derivative on insulin receptors in 3T3-L1 adipocytes. - Weiland, M (1990)
In the present study we describe the antagonistic effects of the covalently dimerized insulin derivative B29,B29'-suberoyl-insulin on insulin receptors in 3T3-L1 mouse cells. In differentiated 3T3-L1 adipocytes, the derivative fully inhibits binding of 125I-labeled insulin to its receptor with about the same affinity as unlabeled insulin. In contrast, the dimerized derivative only partially (approximately 20%) mimics insulin's effects on glucose transport and DNA synthesis in the absence of insulin. In the presence of insulin, the agent competitively inhibits insulin-stimulated DNA synthesis ([3H]thymidine incorporation into total DNA), glucose transport activity (2-deoxyglucose uptake rate), and insulin receptor tyrosine kinase activity. In rat adipocytes, in contrast, the dimerized derivative stimulates glucose transport (initial 3-O-methylglucose as well as 2-deoxyglucose uptake rates) to the same extent as insulin does, and it fails to inhibit the effect of insulin. The data indicate that the dimerized insulin derivative B29,B29'-suberoyl-insulin is an insulin receptor antagonist (partial agonist) which retains a moderate intrinsic activity. The effects of this agent reveal a striking difference in insulin receptor-mediated stimulation of glucose transport between 3T3-L1 fatty fibroblasts and the mature rat adipocyte.